The Meaning of Instructional Supervision for Islamic Religious Education Teachers in Public Elementary Schools - Alwi Ilqam Ma'arif; Rahmat Hariyadi (Kognisi: Jurnal Ilmu Keguruan, 2026)
Instructional supervision is expected to function as professional support rather than merely as administrative control, particularly for Islamic Religious Education (IRE) teachers whose classroom responsibilities combine pedagogical demands with the contextual integration of Islamic values. This study explores how IRE teachers in public elementary schools understand and experience instructional supervision, how supervision is implemented, and which conditions shape its perceived usefulness. A qualitative descriptive case-study design was employed in three public elementary schools in Banyubiru District, Semarang Regency, Indonesia: SDN Banyubiru 01, SDN Banyubiru 03, and SDN Banyubiru 04. Seven informants were selected purposively, comprising three principals, one IRE supervisor, and three IRE teachers. Data were generated through observation, interviews, and document study. Credibility was strengthened through source and method triangulation, member checking, and peer debriefing. Analysis followed data reduction, data display, and conclusion drawing. The findings show that supervision was implemented as a sequence of planning, classroom observation, individual feedback, group supervision, and follow-up. Teachers interpreted effective supervision as a space for reflection, practical problem solving, professional learning, and improvement of instructional planning and classroom practice. Its value was strongest when supervision was scheduled, dialogic, participatory, solution-oriented, and responsive to the local teaching context. Conversely, supervision was perceived as less meaningful when it became document-centered or formalistic. Time constraints and limited integration of technology also emerged as challenges. The study indicates that developmental, collaborative, and context-sensitive supervision is particularly relevant for strengthening IRE teachers' professional practice in elementary schools.